2018
DOI: 10.3389/fped.2018.00175
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Defects and Ciliopathies Associated With Renal Phenotypes

Abstract: Congenital heart disease (CHD) is one of the most common birth defects, and recent studies indicate cilia-related mutations play a central role in the genetic etiology of CHD. As cilia are also known to have important roles in kidney development and disease, it is not surprising that renal anomalies were found to be enriched among CHD mutant mice recovered in a large-scale mouse forward genetic screen. Indeed 42% of mutations identified to cause both CHD and renal anomalies were cilia-related. Many of these ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…However, as patients in our study with renal anomalies also had cardiac defects, it was difficult for us to separate them into these 2 groups. This cooccurrence of both types of birth defects (cardiac and renal anomalies) has been reported in patients, and it has been suggested that there may be a common genetic cause for the occurrence of both anomalies [Gabriel et al, 2018]. The above highlights the fact that one mechanism underlying the physiopathology may be common for all VAC-TERL patients, including those with different clinical features.…”
Section: Discussionmentioning
confidence: 72%
“…However, as patients in our study with renal anomalies also had cardiac defects, it was difficult for us to separate them into these 2 groups. This cooccurrence of both types of birth defects (cardiac and renal anomalies) has been reported in patients, and it has been suggested that there may be a common genetic cause for the occurrence of both anomalies [Gabriel et al, 2018]. The above highlights the fact that one mechanism underlying the physiopathology may be common for all VAC-TERL patients, including those with different clinical features.…”
Section: Discussionmentioning
confidence: 72%
“…Defects in the induction and patterning of the developing kidney can cause congenital anomalies of the kidney and/or urinary tract (CAKUT), a wide range of renal-related birth defects including kidney agenesis, kidney hypoplasia or dysplasia, horseshoe kidney, cystic kidneys, or duplex kidney, as well as multiple collecting ducts or ureters abnormalities (San Agustin et al, 2016 ). Efforts to systematically elucidate genetic link between CAKUT and CHD have been reported, suggesting that CAKUT is highly associated with CHD (Gabriel et al, 2018 ). These findings may allow CHD fetuses benefit from early diagnosis and early therapeutic intervention of CAKUT.…”
Section: Discussionmentioning
confidence: 99%
“…The IC consists of at least three additional proteins: Inversin/NPHP2 (INVS), Serine/threonine-protein kinase NEK8/NPHP9, and ANKS6/NPHP16 [68]. Pathogenic gene variants encoding proteins of the IC cause a spectrum of overlapping phenotypes in humans and rodent models, including cystic kidney disease, cardiovascular abnormalities, and periportal liver fibrosis [68][69][70][71][72][73][74]. Although its assembly hierarchy is characterized, and a link to Wnt and Hippo-signaling established, the role of IC-mediated signaling events remains incompletely understood [68][69][70][71][72][73].…”
Section: The Genetic Basis Of Nephronophthisis (Nphp) and Related Disordersmentioning
confidence: 99%
“…Pathogenic gene variants encoding proteins of the IC cause a spectrum of overlapping phenotypes in humans and rodent models, including cystic kidney disease, cardiovascular abnormalities, and periportal liver fibrosis [68][69][70][71][72][73][74]. Although its assembly hierarchy is characterized, and a link to Wnt and Hippo-signaling established, the role of IC-mediated signaling events remains incompletely understood [68][69][70][71][72][73]. NPHP8/RPGRIP1L controls the assembly of the ciliary transition zone and regulates the ciliary gating function [75].…”
Section: The Genetic Basis Of Nephronophthisis (Nphp) and Related Disordersmentioning
confidence: 99%